Language for Tomorrow: The Fight and Mission to Revive Indigenous Languages in 21st Century Nepal - Rai, Gyanu Maya (NPRC Journal of Multidisciplinary Research, 2025)
Background: Languages are rapidly disappearing around the world in the 21st century. In a multilingual and multicultural country like Nepal, indigenous languages are in danger due to social, political, and institutional neglect. Language extinction not only leads to the loss of identity and culture but also has profound implications for traditional knowledge, local resource management, and social justice.Methodology: This study reviews international and national theoretical and empirical literature. Using research, reports, and data from UNESCO, linguists, and policymakers, it analyses Nepal’s linguistic diversity, conservation efforts, and current challenges.Results: The study shows that policy ambiguity, political instability, resource scarcity, and social neglect have hindered the conservation of indigenous languages in Nepal. Mother tongue-based multilingual education programmes are capital-centric and limited in reach. However, the use of digital technology, community-based campaigns, and support from international organisations has opened up new possibilities for revitalisation.Conclusion: Language conservation is linked to social inclusion, cultural continuity, and equitable development. Conservation of linguistic diversity is possible only through long-term strategies, state-community collaboration, and appropriate use of technology.Novelty: This study highlights the policy-practice gap in multilingual education and proposes technology and community-based measures as strategic solutions.